Application of an ePix100 detector for coherent scattering using a hard X‐ray free‐electron laser. (4th August 2016) - Sikorski, Marcin; Feng, Yiping; Song, Sanghoon; Zhu, Diling; Carini, Gabriella; Herrmann, Sven; Nishimura, Kurtis; Hart, Philip; Robert, Aymeric
Abstract : A prototype unit of the ePix100 camera was used for coherent scattering studies at the Linac Coherent Light Source. The performance of the detector was tested over a broad range of incident flux from 23 down to 0.01 photons per pixel on average. Abstract : A prototype ePix100 detector was used in small‐angle scattering geometry to capture speckle patterns from a static sample using the Linac Coherent Light Source (LCLS) hard X‐ray free‐electron laser at 8.34 keV. The average number of detected photons per pixel per pulse was varied over three orders of magnitude from about 23 down to 0.01 to test the detector performance. At high average photon count rates, the speckle contrast was evaluated by analyzing the probability distribution of the pixel counts at a constant scattering vector for single frames. For very low average photon counts of less than 0.2 per pixel, the `droplet algorithm' was first applied to the patterns for correcting the effect of charge sharing, and then the pixel count statistics of multiple frames were analyzed collectively to extract the speckle contrast. Results obtained using both methods agree within the uncertainty intervals, providing strong experimental evidence for the validity of the statistical analysis. More importantly it confirms the suitability of the ePix100 detector for X‐ray coherent scattering experiments, especially at very low count rates with performances surpassing those of previously available LCLS detectors.